2007
DOI: 10.1177/1352458507076406
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid proteome profile in multiple sclerosis

Abstract: Cerebrospinal fluid (CSF) proteins may provide important information about the pathomechanisms present in multiple sclerosis (MS). Although diagnostic criteria for early MS are available, there is still a need for biomarkers, predicting disease subtype and progression to improve individually tailored treatment. Using the two-dimensional difference gel electrophoresis (2-D-DIGE) technology for comparative analysis, we compared CSF samples from patients with MS of the relapse-remitting type (RRMS, n = 12) and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 46 publications
(48 reference statements)
2
66
2
Order By: Relevance
“…Using two-dimensional difference gel electrophoresis (2-D-DIGE) and MALDI-TOF Mass Spectrometry, Lehmensiek et al [25] have shown a decreased concentration of DBP in the CSF taken during an acute relapse from 12 CIS but not from 12 RRMS cases compared to other neurological diseases (OND). However, another study by Qin et al [33] has shown lower DBP levels in the CSF of 10 RRMS patients at the time of a relapse compared to 10 OND individuals, again using 2D-DIGE and MALDI-TOF Mass Spectrometry.…”
Section: Observationsmentioning
confidence: 99%
“…Using two-dimensional difference gel electrophoresis (2-D-DIGE) and MALDI-TOF Mass Spectrometry, Lehmensiek et al [25] have shown a decreased concentration of DBP in the CSF taken during an acute relapse from 12 CIS but not from 12 RRMS cases compared to other neurological diseases (OND). However, another study by Qin et al [33] has shown lower DBP levels in the CSF of 10 RRMS patients at the time of a relapse compared to 10 OND individuals, again using 2D-DIGE and MALDI-TOF Mass Spectrometry.…”
Section: Observationsmentioning
confidence: 99%
“…Differential gene and protein expression profiles have been generated based on comparative analyses of healthy control and disease-affected tissues derived from clinical samples (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and animal models (19 -29). These biomarker discovery platforms include gel-based approaches such as two-dimensional gel electrophoresis (2D-GE) (10,17,30), 2D-difference image gel electrophoresis (2D-DIGE) (9,14), as well as shotgun proteomics techniques (11,13,16,31,32) incorporating the use of label-free or stable isotope labeling LC-MS-based strategies for quantitative proteomic studies. In recent years there has been exponential growth in the use of these alternative gel-free shotgun proteomics strategies, which has been facilitated by advances in mass spectrometry instrumentation and computational capabilities.…”
mentioning
confidence: 99%
“…Although it is generally classified as a tuner of the immune response, its up-regulation was already shown in pediatric MS [40] and it was discovered to trigger neuronal degeneration [49]. Transferrin is an ironbinding protein reported to be down-regulated in CSF and linked to CIS-MS conversion [44,50]. This could be explained considering its multiple roles on iron metabolism that could affect the formation of myelin sheath, the neurotransmitters synthesis and the oxidative phosphorylation.…”
Section: Image Analysis and Protein Identificationmentioning
confidence: 99%
“…Vitamin D-binding protein acts as a carrier protein for vitamin D and its plasma metabolites, and also serves as a scavenger to clear endotoxins and extracellular G-actin released from necrotic cells. Vitamin D-binding protein has also the capacity to respond in case of acute tissue injury becoming a macrophage-activating factor, a neutrophils chemo-attractant and a C5a-mediated signaling enhancer [40,50,51]. Finally, complement 3 chain C is a degradation product of C3 factor of the complement system, a signal of its activation in the considered district in the presence of a type II or cytotoxic hyper-sensibility.…”
Section: Image Analysis and Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation